Iridium-catalyzed allylic substitutions with cyclometalated phosphoramidite complexes bearing a dibenzocyclooctatetraene ligand: preparation of (π-allyl)Ir complexes and computational and NMR spectroscopic studies - Raskatov, Jevgenij; Jäkel, Mascha; Straub, Bernd Franz; Rominger, Frank; Helmchen, Günter (Chemistry - a European journal, 2012)
(π-Allyl)Ir complexes derived from dibenzocyclooctatetraene and phosphoramidites by cyclometalation are effective catalysts for allylic substitution reactions of linear monosubstituted allylic carbonates. These catalysts provide exceptionally high degrees of regioselectivity and allow the reactions to be run under aerobic conditions. A series of (π-allyl)Ir complexes were prepared and characterized by X-ray crystal structure analyses. An allylic amination with aniline displayed different resting states depending on the presence of a strong base. DFT calculations were carried out on the mechanistic aspects of these reactions. The results suggest that for the (π-allyl)Ir complexes, the formation and reactions with nucleophiles proceed with comparable rates.